Conserved Residues in the C-Terminal Domain Affect the Structure and Function of CYP38 in Arabidopsis - Shi, Lujing; Du, Lele; Wen, Jingru; Zong, Xiumei; Zhao, Wene; Wang, Juan; Xu, Min; Wang, Yuhua; Fu, Aigen (Frontiers in Plant Science, 2021)
Abstract Arabidopsis cyclophilin38 (CYP38) is a thylakoid lumen protein critial for PSII assembly and maintenance, and its C-terminal region serves as the target binding domain. We hypothesized that four conserved residues (R290, F294, Q372, and F374) in the C-terminal domain are critical for the structure and function of CYP38. In yeast two-hybrid and protein pull-down assays, CYP38s with single-sited mutations (R290A, F294A, Q372A, or F374A) did not interact with the CP47 E-loop as the wild-type CYP38. In contrast, CYP38 with the R290A/F294A/Q372A/F374A quadruple mutation could bind the CP47 E-loop. Gene transformation analysis showed that the quadruple mutation prevented CYP38 to efficiently complement the mutant phenotype of cyp38. The C-terminal domain half protein with the quadruple mutation, like the wild-type one, could interact with the N-terminal domain or the CP47 E-loop in vitro. The cyp38 plants expressing CYP38 with the quadruple mutation showed a similar BN-PAGE profile as cyp38, but distinct from the wild type. The CYP38 protein with the quadruple mutation associated with the thylakoid membrane less efficiently than the wild-type CYP38. We concluded that these four conserved residues are indispensable as changes of all these residues together resulted in a subtle conformational change of CYP38 and reduced its intramolecular N-C interaction and the ability to associate with the thylakoid membrane, thus impairing its function in chloroplast.